Quality assurance in an international higher education area : a case study approach and comparative analysis - Bernhard, Andrea; Pechar, Hans. (Wiesbaden : VS Verlag für Sozialwissenschaften, 2012)
Suitable for academics and policy makers in the field of higher education, this title highlights the leading trend towards quality assurance within an international higher education area and provides recommendations to establish a functioning quality assurance system within the observed higher education systems and beyond their borders.
Diss.-- University of Klagenfurt, 2011.
Includes bibliographical references (pages [261]-285).
IQAC
Trim Education
Keywords: Education, Higher -- Evaluation; Higher education and state